Business Strategies of Tegal Food Stalls (Warteg) and Their Influence on Community Buying Interest in Makassar - Sulfati, Andi; Rapanna, Patta; Hernita, Hernita (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
The type of research is qualitative through a phenomenological approach, while the results show that Warteg or warung tegal is one of the popular culinary businesses in Makassar City because it serves delicious, affordable, and diverse food. To increase people's buying interest at night, strategies are needed such as providing menus that suit nighttime preferences, for example fried or healthy food; keeping prices affordable with discount promotions; ensuring strategic locations and easy access; and utilising technology through delivery applications and social media for promotion. Improved service quality, cleanliness, and unique experiences such as special events can also attract customers. Partnerships with local communities and the implementation of a reward system for loyal customers also strengthen the appeal of this business. With effective and innovative strategies, warteg can continue to grow and compete in Makassar's night food marketThe type of research is qualitative through a phenomenological approach, while the results show that Warteg or warung tegal is one of the popular culinary businesses in Makassar City because it serves delicious, affordable, and diverse food. To increase people's buying interest at night, strategies are needed such as providing menus that suit nighttime preferences, for example fried or healthy food; keeping prices affordable with discount promotions; ensuring strategic locations and easy access; and utilising technology through delivery applications and social media for promotion. Improved service quality, cleanliness, and unique experiences such as special events can also attract customers. Partnerships with local communities and the implementation of a reward system for loyal customers also strengthen the appeal of this business. With effective and innovative strategies, warteg can continue to grow and compete in Makassar's night food market.